2019
DOI: 10.3390/s19224842
|View full text |Cite
|
Sign up to set email alerts
|

New Concept of Combined Microwave Delay Lines for Noise Radar-Based Remote Sensors

Abstract: Delay lines with a tunable length are used in a number of applications in the field of microwave techniques. The digitally-controlled analogue wideband delay line is particularly useful in noise radar applications as a precise detector of movement. In order to perform coherent reception in the noise radar, a delay line with a variable delay value is required. To address this issue, this paper comprises a new concept of a digitally-controlled delay line with a set of fine distance gates. In the paper, a solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…The time-delay parameter is playing a capital role in the communication system in the different areas as in RF and microwave area (Wijenayake et al, 2012;Scalora et al, 1996;Condon et al, 2004). The delay effect can also be exploited to design different functions (Nabekawa and Midorikawa, 2004;Narasimhan et al, 2005;Vemagiri et al, 2007;Herrojo et al, 2019;Park et al, 2007;Szczepaniak and Susek, 2019). The group delay (GD) dispersion was exploited to design an indirect phase control mixer (Nabekawa and Midorikawa, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The time-delay parameter is playing a capital role in the communication system in the different areas as in RF and microwave area (Wijenayake et al, 2012;Scalora et al, 1996;Condon et al, 2004). The delay effect can also be exploited to design different functions (Nabekawa and Midorikawa, 2004;Narasimhan et al, 2005;Vemagiri et al, 2007;Herrojo et al, 2019;Park et al, 2007;Szczepaniak and Susek, 2019). The group delay (GD) dispersion was exploited to design an indirect phase control mixer (Nabekawa and Midorikawa, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The transmission line (TL) delay was used to implement an RFID system (Vemagiri et al, 2007;Herrojo et al, 2019). Further, research works were conducted on the GD adjustment (Park et al, 2007;Szczepaniak and Susek, 2019;Song, 2008). Behind those classical exploitations of GDs, it was also found that the GD effect can be compensated by using the negative GD (NGD) function Broomfield and Everard, 2000;Meng et al, 2018;Shao et al, 2020).…”
Section: Introductionmentioning
confidence: 99%